2008
DOI: 10.1016/j.carres.2007.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected formation of complex bridged tetrazoles via intramolecular 1,3-dipolar cycloaddition of 1,2-O-cyanoalkylidene derivatives of 3-azido-3-deoxy-d-allose

Abstract: Abstract-An unexpected and interesting intramolecular side reaction occurred during the attempted synthesis of glycosyl cyanides upon treatment of 1-O-acetyl-3-azido-3-deoxyallose derivatives with TMSCN and different Lewis acids. Exo-1,2-O-cyanoalkylidene derivatives formed by neighboring group participation and attack of cyanide underwent, after Lewis-acid mediated isomerization to the endo-isomer, intramolecular azide-cyanide cycloaddition leading to the formation of tetrazoles embedded in bridged tetracycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Unexpected reaction from intramolecular 1,3-dipolar cycloaddition of 1,2-O-cyanoalkylidene derivatives of 3-azido-3-deoxy-D-allose (Worch & Wittmann, 2008) 6 α-Carba-β -D-fructopyranose…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 98%
“…Unexpected reaction from intramolecular 1,3-dipolar cycloaddition of 1,2-O-cyanoalkylidene derivatives of 3-azido-3-deoxy-D-allose (Worch & Wittmann, 2008) 6 α-Carba-β -D-fructopyranose…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 98%
“…By contrast to what we observed for 1a , the reaction of 11 in the presence of sodium azide in DMF at 80 °C for 48 h, led to the recovery of the unchanged starting material. Heating at reflux a toluene solution of 11 for 24 h was also unsuccessful for converting this azido-cyanide into its [3 + 2] cycloadduct, the tetracyclic 1,4-diazepine 12 , which however was obtained in 66% yield after heating 11 at 140 °C in DMF solution for 48 h.…”
Section: Resultsmentioning
confidence: 99%
“…We decided to use an ester protecting group at position 2 of the diamino ribose to control the stereochemistry of this step by neighboring group participation. However, it had been reported that furanoses with an acetyl group at position 2 can lead to the formation of 1,2- O -cyanoethylidene derivatives . Indeed, attempts to employ 1,2-di- O -acetyl-3-azido-3,5-dideoxy-5-phthalimido- d -ribofuranose, which was obtained in two steps from 11 , in a C-glycosylation reaction (TMS-CN, SnCl 4 , CH 2 Cl 2 ) failed and gave predominantly the corresponding 1,2- O -cyanoethylidene derivative (data not shown).…”
Section: Results and Discussionmentioning
confidence: 99%